Post-2000 milestones in freshwater fish taxonomy: a comprehensive review of newly described species in Türkiye - Cüneyt Kaya; Gülşah Saç; Nicolas Hubert; Mert Minaz; Irmak Kurtul (Zoosystematics and Evolution)
The 2000s are the revolutionary decade for the taxonomy of freshwater fishes of Türkiye in terms of the most significant ever rate of increase in species descriptions. Among the approximately 390 freshwater fish species reported from Türkiye, a remarkable 136 have been described since 2000, reflecting an accelerated pace of taxonomic and morphological activity. This surge has been prompted by the influx of new researchers and the widespread adoption of molecular sequencing techniques, currently at the center of taxonomic work since the 2010s. This synthesis gives a complete view of these 136 new species named, examining predominant parameters such as genera, descriptors, contributing countries, and the chronological order of discoveries. The results are presented through visual data, which help illustrate the progress in taxonomic research and the contributions of international collaboration. The study also highlights the rapid development of freshwater biodiversity research in Türkiye and emphasizes the value of using integrated methods and global partnerships to better understand less-studied aquatic species. The bibliometric analysis indicates that a substantial proportion of new species descriptions is ascribed to a limited cohort of prolific researchers, with the majority of contributions made by a core group of the top 10 authors. These discoveries not only augment our comprehension of Türkiye’s freshwater fish fauna but also illuminate broader trends influencing taxonomic study in the 21st century.